Electrochemical Immunoassay for Cytomegalovirus Antigen Detection with Multiple Signal Amplification Using HRP and Pt‐Pd Nanoparticles Functionalized Single‐walled Carbon Nanohorns. Issue 5 (12th January 2016) - Huang, Weiwei; Xiang, Guiming; Jiang, Dongneng; Liu, Linlin; Liu, Chang; Liu, Fei; Pu, Xiaoyun
Abstract: Cytomegalovirus is typically associated with immunocompromised hosts, pregnant women and transplant patients, who require a timely diagnosis. In this work, a sensitive and highly specific electrochemical amplification immunosensor was established for detecting Cytomegalovirus pp65 antigen based on Pt‐PdNPs@SWCNHs with horseradish peroxidase (HRP) as a signal enhancer and thionine as a signal probe. First, Pt nanoparticle (PtNP) and Pd nanoparticle (PdNP) functionalized single‐walled carbon nanohorn (SWCNH) nanocomposites, i.e. Pt‐PdNPs@SWCNHs, was used as a carrier for immobilization of antibody through the Pt‐N bond and the Pd‐N bond. Next, HRP was used to block the rest of the binding‐sites. Signal amplification was obtained by the cooperative catalytic activities of Pt‐PdNPs and HRP to H2 O2 . SWCNHs loaded with a large amount of Pt‐PdNPs further amplified the signal due to the excellent surface area. The fabricated immunosensor was used to detect different concentrations of Cytomegalovirus pp65 antigen under optimized conditions. The tests showed a linear range from 0.1 to 80 ng mL −1 with a low detection limit of 30 pg mL −1, and exhibited excellent selectivity, stability and reproducibility. Therefore, this project presented a potential approach for the early diagnosis of Cytomegalovirus infection in clinical trials. Abstract :